A rare complication of radiofrequency treatment for cellulite of the lower leg. (September 2022) - Ulrich, F.; Elahi, L.; Schiraldi, L.; Grobbelaar, A.; Raffoul, W.
Abstract: Radiofrequency (RF) is increasingly used as an aesthetic treatment for a variety of purposes ranging from the treatment of acne scarring, cellulite correction and skin and soft tissue rejuvenation. The majority of patients experience no complications, and the treatment is therefore also frequently administered by non-medically trained staff. We present a patient, who developed severe 3rd degree burn after RF treatment requiring reconstructive surgery with a split thickness skin graft.